2021
DOI: 10.1002/hbm.25408
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV‐infection on human somatosensory processing, spontaneous cortical activity, and cortical thickness: A multimodal neuroimaging approach

Abstract: HIV‐infection has been associated with widespread alterations in brain structure and function, although few studies have examined whether such aberrations are co‐localized and the degree to which clinical and cognitive metrics are related. We examine this question in the somatosensory system using high‐resolution structural MRI (sMRI) and magnetoencephalographic (MEG) imaging of neural oscillatory activity. Forty‐four participants with HIV (PWH) and 55 demographically‐matched uninfected controls completed a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…To identify the impact of Alzheimer’s disease and HAND pathologies on somatosensory gating and be consistent with previous studies, 13 , 14 , 40 we computed the gating ratio (i.e. response to Stimulation 2 divided by the response to Stimulation 1) and ran a 3 × 1 ANOVA.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…To identify the impact of Alzheimer’s disease and HAND pathologies on somatosensory gating and be consistent with previous studies, 13 , 14 , 40 we computed the gating ratio (i.e. response to Stimulation 2 divided by the response to Stimulation 1) and ran a 3 × 1 ANOVA.…”
Section: Resultsmentioning
confidence: 79%
“… 13 , 15 , 36–39 While numerous studies have found aberrant auditory gating in Alzheimer’s disease, somatosensory gating has been examined only once in Alzheimer’s disease 40 and only a handful of times in HAND. 13–15 To the best of our knowledge, no study to date has compared somatosensory gating deficits in participants with HAND versus those with Alzheimer’s disease. Thus, whether differences in gating and somatosensory processing more broadly can distinguish those with Alzheimer’s disease and HAND remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Somatosensory function has been found to be impaired in a number of other neurological, developmental, and psychiatric disorders, including Parkinson's disease [58] , HIV-associated neurocognitive disorders [ 42 , [59] , [60] , [61] ], autism [62] , cerebral palsy [ 63 , 64 ], schizophrenia [65] , and others. Typically, such deficits are indicated by a reduced neural response to somatosensory stimuli, however, our findings indicate the inverse in AD: a hyper-sensitivity to stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent papers have focused on structural measures such as cortical thickness, surface area, and gyrification [62, 65 •, 66] that have increasingly been used in studies of HIV among children [67], as well as adults [68][69][70][71][72], and are sensitive to developmental processes. The few studies focusing on adolescents and young adults show regionally specific decreases in cortical thickness, including temporal, orbitofrontal, and occipital lobes in combination with lower gray matter volume in subcortical structures among Spanish young adults [62], decreased cortical thickness in right temporal lobe and fusiform gyrus among Zambian adolescents with PHIV [73], and increased thickness in left occipital and right olfactory areas and decreased cortical thickness in temporal and orbitofrontal regions among Chinese youth [60].…”
Section: Selected Recent Neuroimaging Studies Among Adolescents and Y...mentioning
confidence: 99%